2019
DOI: 10.32615/ps.2019.114
|View full text |Cite
|
Sign up to set email alerts
|

Foliar application of selenium (Se) at heading stage induces regulation of photosynthesis, yield formation, and quality characteristics in fragrant rice

Abstract: In order to study the effect of foliar application of sodium selenate on fragrant rice performance at the heading stage, the present study was conducted with two fragrant rice cultivars, 'Meixiangzhan-2' and 'Xiangyaxiangzhan'. At the heading stage, six concentrations of sodium selenate solution (0, 10, 20, 30, 40, and 50 μmol L-1) were sprinkled to plants. Our results showed that foliar application of sodium selenate increased chlorophyll contents in rice leaves and upregulated net photosynthetic rate at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…Therefore, compared with rotary, as plow tillage causes less soil fragmentation, it is relatively more highly conducive to soil conservation, which might be the main reason underlying the observed increment in soil organic matter in these experiments (Du et al, 2019a;Du et al, 2019b). Grain quality attributes including, milling, appearance, nutrient content, texture, and aroma greatly affect the market price of fragrant rice, thus directly influencing the economy of fragrant rice production (Luo et al, 2019b). Here, we observed that continuous plow tillage not only improved grain 2-AP content, additionally, it increased grain protein content while decreasing grain amylose content.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Therefore, compared with rotary, as plow tillage causes less soil fragmentation, it is relatively more highly conducive to soil conservation, which might be the main reason underlying the observed increment in soil organic matter in these experiments (Du et al, 2019a;Du et al, 2019b). Grain quality attributes including, milling, appearance, nutrient content, texture, and aroma greatly affect the market price of fragrant rice, thus directly influencing the economy of fragrant rice production (Luo et al, 2019b). Here, we observed that continuous plow tillage not only improved grain 2-AP content, additionally, it increased grain protein content while decreasing grain amylose content.…”
Section: Discussionmentioning
confidence: 91%
“…Grain quality attributes including, milling, appearance, nutrient content, texture, and aroma greatly affect the market price of fragrant rice, thus directly influencing the economy of fragrant rice production (Luo et al., 2019b). Here, we observed that continuous plow tillage not only improved grain 2‐AP content, additionally, it increased grain protein content while decreasing grain amylose content.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of Luo et al. (2019c) also indicated the application of Se fertilizer was able to promote the fragrant rice productivity and grain quality by increasing the chlorophyll concentration and enhancing the net photosynthetic rate.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, under machine-transplanted and machine-direct seeded rice system, rice is distributed in rows in the field with the same plant spacing and thus, the ventilation and lighting will be good (Pan et al, 2017;Huang et al, 2018b). Better ventilation and lighting conditions would lead to the better gas exchange as well as higher net photosynthetic rate of rice and increase DM accumulation and enhance yield formation (Luo et al, 2019). Therefore, we deduced that uniform horizontal distribution of fragrant rice in paddy field under MT and MDS treatments enhanced the canopy apparent photosynthesis and led to the improvement in DM accumulation and yield formation.…”
Section: Discussionmentioning
confidence: 99%